Beta-synuclein in cerebrospinal fluid as an early diagnostic marker of Alzheimer’s disease - Halbgebauer, Steffen; Oeckl, Patrick; Steinacker, Petra; Yilmazer-Hanke, Deniz; Straub, Sarah; Arnim, Christine von; Frölich, Lutz; Gomes, Luis Aragão; Hausner, Lucrezia; Huss, André Michael; Jahn, Holger; Weishaupt, Jochen H.; et al. (Journal of neurology, neurosurgery, and psychiatry, 2021)
Objective Synaptic loss plays a major role in Alzheimer’s disease (AD). However so far no neurochemical marker for synaptic loss has been introduced into clinical routine. By mass spectrometry beta-synuclein was established as a candidate marker. We now aimed to set up a novel ELISA for beta-synuclein for evaluation of its potential as a diagnostic and predictive marker for AD. - Methods We analysed in total 393 patients from four specialised centres. The diagnostic groups comprised: AD (n=151), behavioural variant frontotemporal dementia (bvFTD, n=18), Parkinson syndrome (n=46), Creutzfeldt-Jakob disease (CJD, n=23), amyotrophic lateral sclerosis (ALS, n=29), disease control (n=66) and 60 non-neurodegenerative control patients. Results were compared with core AD biomarkers (total tau, phospho-tau and amyloid-β peptide 1-42). Additionally, coexistence of beta-synuclein with vesicular glutamate transporter 1 (VGLUT1) was determined and beta-synuclein levels were quantified in brain homogenates. - Results Beta-synuclein levels quantified with the newly established ELISA correlated strongly with antibody-free quantitative mass spectrometry data (r=0.92 (95% CI: 0.89 to 0.94), p<0.0001). Cerebrospinal fluid (CSF) beta-synuclein levels were increased in AD-mild cognitive impairment (p<0.0001), AD dementia (p<0.0001) and CJD (p<0.0001), but not in bvFTD, Parkinson syndrome or ALS. Furthermore, beta-synuclein was localised in VGLUT1-positive glutamatergic synapses, and its expression was significantly reduced in brain tissue from patients with AD (p<0.01). - Conclusion We successfully established a sensitive and robust ELISA for the measurement of brain-enriched beta-synuclein, which we could show is localised in glutamatergic synapses. We confirmed previous, mass spectrometry-based observations of increased beta-synuclein levels in CSF of patients with AD and CJD supporting its potential use as a marker of synaptic degeneration.